Advanced nondestructive evaluation II : proceedings of the International Conference on ANDE 2007, the 2nd International Conference on Advanced Nondestructive Testing - Lee, Seung-Seok (World Scientific Pub. Co., 2008)
This volume comprises papers presented at the 2nd International Conference on Advanced Nondestructive Evaluation (ANDE 2007) held in Busan, Korea, on October 17-19, 2007. Many of the excellent papers included in this book show the current state of nondestructive technologies, which are experiencing rapid progress with the integration of emerging technologies in various fields. As such, this volume provides an avenue for both specialists and scholars to share their ideas and the results of their findings in the field of nondestructive evaluation.